Analisis Kestabilan Lereng Highwall Tambang Batubara Pit X Pada Kabupaten Balangan, Kalimantan Selatan - Andewa Fitru Fadhlurohman; Daniel Radityo (Jurnal Ilmiah Geologi PANGEA, 2025)
Coal mining is generally carried out using the open-pit method, which results in the formation of surrounding slopes. Slope stability analysis is essential to determine the safety factor value and prevent potential landslides. This study aims to identify the rock formations and determine the safety factor of the highwall slope in pit “X.” Administratively, the study area is located in Balangan Regency, South Kalimantan Province. The research methodology includes field mapping to obtain primary data on lithology types and orientations, as well as the scanline method on the rock slope to determine the Geological Strength Index (GSI). Secondary data obtained from the company include slope design data, current topography, laboratory test results of rock samples, and groundwater level data. Slope stability analysis was conducted on six cross-sections, from section A–A’ to section F–F’, along the highwall using the Limit Equilibrium Method (LEM) with the Morgenstern-Price approach and the Generalized Hoek-Brown failure criterion. The analysis was performed under both static and dynamic conditions with a horizontal seismic coefficient of 0.05. The results show that all six slope sections have safety factor values greater than 1.3 under static conditions and greater than 1.1 under dynamic conditions, indicating that the slopes are classified as stable.